Rational Expectations and the Impact of Money Upon Stock Prices - Sorensen, Eric H. (Journal of Financial and Quantitative Analysis, 1982)
Received monetary theory supports the existence of a strong relationship between monetary activity and stock prices. Following the work of Friedman and Schwartz [8], relating money supply to aggregate economic activity, some researchers have examined the more specific connection between changes in the rate of growth of money supply and associated movements in stock prices (see [6], [10], [11], [14], [17], [18], [19], [20], [22], and [28]). These studies use a variety of monetary aggregate measures to functionally relate the level of stock market indices to contemporaneous and lagged monetary growth rates. In general, the findings indicate a direct relationship between money supply and stock returns.